Background DNA on flooring: The effect of cleaning. Issue 1 (December 2019) - Reither, J.B.; Gray, E.; Durdle, A.; Conlan, X.A.; van Oorschot, R.A.H.; Szkuta, B.
Abstract: The collection and detection of 'background' DNA (bDNA) from items submitted for forensic DNA sampling is a common occurrence when sampling surfaces for DNA left behind following an activity of interest. There are a number of factors that might affect the presence of bDNA on a surface, one of which is cleaning of the surface. Here, we investigate the impact of household cleaning methods on the presence of bDNA on flooring in five homes occupied by known and unrelated individuals. Two adjacent samples were collected pre- and post-cleaning from areas of high and low activity on floors within the kitchen, living room, bedroom and bathroom (i.e. four samples per room). Floors were cleaned by the participant according to their normal routine, with methods and products varying between rooms and homes. Overall, slightly greater quantities of DNA were obtained from samples taken prior to cleaning compared to post-cleaning. Further, major contributors were more frequently assigned in profiles from samples obtained pre-cleaning, although the number of contributors was generally greater in these profiles. This study highlights the need to consider domestic cleaning histories of a surface from which a sample is collected.